Chemical Speciation of Thorium in Marine Biogenic Particulate Matter - Katsumi Hirose (The Scientific World Journal)
Concentrations of particulate thorium in seawater were determined together with the strong organic ligand (SOL) and uranium in particulate matter (PM). The concentrations of particulate Th in surface waters of the western North Pacific and the Sea of Japan ranged from 0.05 to 1.5 pM (1 x 10−12 M), and showed relatively large temporal and spatial variations. In order to chemically characterize the particulate Th in seawater, the relationship between particulate Th and SOL concentrations in surface PM was examined. The result reveals that particulate Th in surface PM was well correlated with the SOL concentration in PM. The concentrations of particulate Th in surface water were linearly related to those of particulate U. Mass balance analysis suggests that the dominant chemical form of Th(IV), as well as of U, in surface PM is a surface complex with the SOL in PM. Our findings suggest that the SOL in PM is a nonmetal-specific chelator originating from the cell surface of microorganisms.